"Trident" preputial plasty for phimosis in childhood. Issue 3 (June 2017) - Pedersini, Pierluigi; Parolini, Filippo; Bulotta, Anna Lavinia; Alberti, Daniele
Summary: Objective: To evaluate the functional and cosmetic result of modified-triple incision preputial plasty for surgical management of phimosis in children. Materials and methods: This prospective study involved all consecutive children (age 3–15) with phimosis, managed at our Institution in a one–year period. All patients unable to retract the foreskin and symptomatic with episodes of posthitis or balanoposthitis or ballooning of the foreskin with voiding were initially included. After a two-month trial of topic corticosteroids treatment, for patients refractory to conservative ointment treatment, "trident" preputial plasty was offered. This procedure combines two lateral Z-plasty and one middle Y–V plasty. All the procedures were performed as a day care, in general anaesthesia by two senior surgeons. Outpatient follow-up controls were scheduled at 1 and 2 week, 1, 6 and 12 months after surgery, respectively. Results: A total of 41 patient were enrolled. Mean operative time was 24 minutes (range 15–43). At 12-month follow-up, all but one patients (97.6%) was able to retract the prepuce. Cosmetic and functional results were satisfactory. Conclusion: In selected group of children with phimosis, the "trident" preputial plasty provided excellent cosmetic and functional result. Adequate retraction of the prepuce by the patients soon after surgery is mandatory.